2012
DOI: 10.1007/s10554-012-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right ventricular function by three-dimensional echocardiography and myocardial strain imaging in adult atrial septal defect before and after percutaneous closure

Abstract: Real-time three-dimensional (3D) echocardiography allows us to measure right ventricular (RV) end-diastolic volume irrespective of its shape. Tissue Doppler imaging (TDI) and speckle tracking imaging (STI) are new tools to assess myocardial function. We sought to evaluate RV function by 3D echocardiography and myocardial strain imaging in adult patients with atrial septal defect (ASD) before and 6 months after transcatheter closure in order to assess the utility of these new indexes in comparison with standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 44 publications
5
50
0
1
Order By: Relevance
“…We have already shown in previous reports (26,28) that the newer technologies appear to be superior to the older technologies, including RVFAC, TAPSE, and MPI. Compared to RVFAC, MPI and TAPSE, 3D-RVEF had a stronger correlation with MRI, and the assessment of 3D-RVEF and RV strain allowed a better prediction of unfavorable outcome after ASD closure (26).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…We have already shown in previous reports (26,28) that the newer technologies appear to be superior to the older technologies, including RVFAC, TAPSE, and MPI. Compared to RVFAC, MPI and TAPSE, 3D-RVEF had a stronger correlation with MRI, and the assessment of 3D-RVEF and RV strain allowed a better prediction of unfavorable outcome after ASD closure (26).…”
Section: Discussionmentioning
confidence: 78%
“…Compared to RVFAC, MPI and TAPSE, 3D-RVEF had a stronger correlation with MRI, and the assessment of 3D-RVEF and RV strain allowed a better prediction of unfavorable outcome after ASD closure (26). Moreover,…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The increased myocardial strain values return to normal after ASD closure. Vitarelli et al [40] reported that RV longitudinal strain were significantly higher than control group before percutaneous closure and decreased significantly after closure [40].…”
Section: Discussionmentioning
confidence: 99%
“…Viteralli ve arkadaşları (18), perkütan atriyal septal defekt kapatılan hastalarda üç boyutlu ekokardiyografi ile strain ve SRI değerlendirmesi yapmıştır. Kapatılma sonrası sağ ventrikülün ejeksiyon fraksiyonunda ve strain ölçümlerinde anlamlı azalma olduğunu göstermiştir (18). Bunun hakim yükünün azalmasına bağlı olduğunu söylemişlerdir.…”
Section: Discussionunclassified